Emerging psychosocial factors and work overload perceptions of Mexican university teachers and students working and studying from home during the COVID-19 pandemic - Quezada Díaz, Belem; Hindrichs, Imke; Castellanos Simons, Doris (Frontiers in Psychology, 2024)
In Mexico, academic activities during the Covid-19 pandemic were performed from home for over two years. Especially during the first months of the pandemic, the particular conditions of lockdown resulted in a re-organization and a new understanding of social dynamics. Therefore, the objective of this paper was to explore the perception of university students and teachers regarding emerging psychosocial factors that either encourage or hinder work and/or study from home during the confinement, as well as their perception of work overload. Furthermore, the differences between students and teachers in the studied variables were analyzed. A predominantly quantitative, cross-sectional, and correlational study was conducted with N=108 participants (42.6% university teachers; 57.4% graduate or postgraduate students) who answered an online questionnaire encompassing: two openended inductors to indicate positive and negative aspects of working or studying from home and their frequency of perception, the Covid-19 Work Overload from Home Scale (ESTC-COVID19) and questions about the hours a day devoted to different activities. The open responses were categorized by two independent groups of the research team; the emerging categories were then consensually agreed and further transformed into dummy and continuous variables. These variables and the results of the ESTC-COVID19 were analyzed with SPSS 19 by means of Pearson correlations, as well as Chi-Square test and Student's ttest. Results show the 9 positive and 10 negative emerging psychosocial factors, to which open answers of at least 10% of the sample were attributed. In addition, Work overload correlated negatively with the emerging factor "Making better use of time", and positively with "Work, school and/or domestic activities overload"; moreover, students perceived more work overload than teachers. Finally, differences between students and teachers were observed in the following psychosocial factors (observing a general tendency of more discomfort perceived by students): "Self-management", "Comfort", "Enjoying home" (as positive factors), and "Domestic work" and "Interruptions, distractors, noise" (as negative factors). The paper analyzes these differences in terms of the demands and nature of the study and work activities undertaken by both groups, as well as the previous training of the skills and the resources required to carry them out.